2023
DOI: 10.1002/adma.202211260
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Valent Manganese Atoms Stabilized on Ceria for Nitrous Oxide Synthesis

Abstract: Nitrous oxide, N2O, exhibits unique reactivity in oxidation catalysis, but the high manufacturing costs limit its prospective uses. Direct oxidation of ammonia, NH3, to N2O can ameliorate this issue but its implementation is thwarted by suboptimal catalyst selectivity and stability, and the lack of established structure–performance relationships. Systematic and controlled material nanostructuring offers an innovative approach for advancement in catalyst design. Herein low‐valent manganese atoms stabilized on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The catalytic performance in ammonia oxidation was evaluated at atmospheric pressure in a fixed-bed microreactor (Figure S1). , The gases, He (PanGas, purity 4.6, diluent), NH 3 (PanGas, purity 3.8), O 2 (PanGas, purity 5.0), and Ar (PanGas, purity 5.0, internal standard), were fed using thermal mass-flow controllers (Bronkhorst), connected to a mixing unit equipped with a pressure gauge. The catalyst [particle size = 0.15–0.4 mm, m cat = 0.002–0.2 g for kinetic tests, and 0.05 g for stability tests; for tests at elevated GHSV (>15,000 cm 3 h –1 g cat –1 ) the catalyst bed was diluted with SiC (particle size = 0.5–0.6 mm) to minimize the formation of hot spots] was loaded into a quartz microreactor (inner diameter = 8 mm for m cat > 0.03 g or 2 mm for m cat < 0.03 g), containing a bed made of quartz wool and placed in an electrical oven.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalytic performance in ammonia oxidation was evaluated at atmospheric pressure in a fixed-bed microreactor (Figure S1). , The gases, He (PanGas, purity 4.6, diluent), NH 3 (PanGas, purity 3.8), O 2 (PanGas, purity 5.0), and Ar (PanGas, purity 5.0, internal standard), were fed using thermal mass-flow controllers (Bronkhorst), connected to a mixing unit equipped with a pressure gauge. The catalyst [particle size = 0.15–0.4 mm, m cat = 0.002–0.2 g for kinetic tests, and 0.05 g for stability tests; for tests at elevated GHSV (>15,000 cm 3 h –1 g cat –1 ) the catalyst bed was diluted with SiC (particle size = 0.5–0.6 mm) to minimize the formation of hot spots] was loaded into a quartz microreactor (inner diameter = 8 mm for m cat > 0.03 g or 2 mm for m cat < 0.03 g), containing a bed made of quartz wool and placed in an electrical oven.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Instead, propelled by the recent advances in the field of blue and green NH 3 production, direct NH 3 oxidation to N 2 O has emerged as a more efficient and sustainable synthesis method but requires the design of a suitable catalyst. In this endeavor, manganese oxide-based materials have been most widely investigated, leading to the discovery of a promising Mn–Bi–O/α-Al 2 O 3 system at the Boreskov Institute of Catalysis . Still, issues of suboptimal N 2 O selectivity, catalyst deactivation, and the necessity to work in excess of O 2 , incurring significant downstream costs, have precluded commercialization. , Recently, our group has reported CeO 2 -supported gold nanoparticles and low-valent manganese single atoms as highly efficient catalysts for NH 3 oxidation to N 2 O. , Leveraging the redox properties of CeO 2 has enabled operation under stoichiometric conditions achieving N 2 O selectivity above 80% and 3- to 4-fold higher productivity per gram of catalyst than Mn–Bi–O/α-Al 2 O 3 . This has demonstrated that precise control over the nanostructure of the metal and the properties of the carrier are key to maximizing the catalytic effect , and could be translated to other underexplored materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of single-atom catalysts (SACs) by dispersing metals onto selected supports, such as zeolites, MOFs, COFs, carbon carriers, oxides, and carbon-nitride, has seen a recent surge in designing efficient heterogeneous catalysts. This strategy undoubtedly enhances the use of isolated dispersed metal atoms, providing more active sites compared to the corresponding metal clusters and nanoparticle forms. , Practically, it has been proven that, relative to the use of the basic support materials, SACs can enhance the catalytic reactivity and selectivity in specific reactions. Furthermore, exploiting the advances in X-ray absorption near edge structure (XANES), , extended X-ray absorption fine structure (EXAFS), and solid-state nuclear magnetic resonance (NMR), a complete picture of the heterogeneous catalytic processes can be provided in some cases. , While metals such as Fe, Ni, Ru, and Pt have been extensively investigated as SACs, other 3d transition metals (from Sc to Mn) have been less explored due to their lower reactivity, even though they are less toxic and expensive. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, in catalytic oxidation reactions, CeO 2 -based catalysts always exhibit superior catalytic performance because of their excellent oxygen storage and release capacity. 27,28 Fabrication of mesoporous CeO 2 supporting materials with a high surface area and mesopores that can strengthen mass transfer during the reaction is still a research challenge.…”
Section: Introductionmentioning
confidence: 99%